Building Strategic Partnership of Transnational Education Using Online Program to Increase Academic Quality of Graduates - Polla, Gerardus (ComTech: Computer, Mathematics and Engineering Applications, 2011)
International employment standard requires higher quality of graduates, which can be achieved through high quality academic standards. As we know there are still a large number of graduates of Indonesian higher education rejected to work in global industry. Besides having low GPA, lots of graduates are considered lacking technical skills, interpersonal skills, and international experience. Indeed, the main weakness factor is the low English proficiency of graduates. We need a breakthrough that develops our academic standards of higher education to obtain international quality. Yet, there are challenges to face by the government, such as rebuilding the national system (establishing elite institutions), internationalizing higher education (globalizing the institutions or cross-border trades of education services), as well as enhancing private participation by repositioning the private sector. To overcome these challenges we need to build a strategic partnership of transnational education using online programs, which can obtain mutual benefit for the collaborating institutions. This article discusses about how to increase academic quality of graduates in Indonesia or in other Asian countries.